Miscellanea Chorologica Occidentalia, III - Sánchez- Mata, Daniel; Gavilán, Rosario G.; Luengo Nicolau, Enrique; Rodríguez-Rojo, Pilar (Lazaroa, 2001)
Several records of vascular plants collected in the central-western territories of the Iberian Peninsula are provided, with comments about their regional chorological interest.